Healing Effect of Sesame Ointment on Second-degree Burn Wound in Rats: - Jangholi, Ehsan; Tehrani, Setareh; Lotfi, Parisa; Tehrani, Sepideh; Aryan, Hoda; Aidun, Amir (Galen Medical Journal, 2016)
Background: Wound healing requires processes like cell migration, proliferation of extracellular matrix deposition, remodeling and angiogenesis. Also, anti-oxidative and anti-inflammatory reactions play key roles in the progression of wound healing. Previous studies showed that sesame oil has anti-inflammatory, antimicrobial and antioxidant activities. In addition, it is shown that sesame oil stimulates fibroblast production in vitro and in skin wounds. Therefore, in this study we investigated the effects of sesame ointment on the process of second-degree burn wound healing in rat models according to stereological parameters. Materials and Methods: In this experimental study, forty male Wistar rats (200±20 g) were randomly divided into four groups (n=10): ointment-base treated group (vehicle), silver sulfadiazine (SDD) treated group, sesame treated group (E1) and the control group which received no treatment. A 2×3 cm2 standard second-degree burn wound was induced on the posterior surface of animal’s neck under general anesthesia. After sacrifice, the animal’s skin sample was fixed in buffered formaldehyde for stereological evaluations. The data was analyzed by SPSS statistical software (version 14.0). P<0.05 was considered statistically significant. Results: According to our results, the mean of reduction in wound areas, volume density of collagen bundles and hair folicules, fibroblast populations, length density of vessels in E1 group was significantly higher than control group (P<0.05). The differences between E1 and SSD were not statistically noticeable regarding the stereological parameters. Conclusion: According to stereological analysis, administration of sesame ointment showed the ability to improve wound healing process and tissue regeneration in the treatment of skin damages.[GMJ.2016;5(2):56-62]